Income redistribution, inequality and democracy : a political economy approach - Hwan, Joo Seo; Sung, Jin Kang (New York, NY : Routledge, 2024)
"This book answers why democracy has failed to deliver effective solutions to income inequality problems over the last four decades, and if democracy can offer solutions to various increases in inequality in the future. It also addresses what elements are necessary for democracy to serve as an effective alternative for addressing inequality issues. Historical experiences over the past 40 years, including the global financial crisis, not only underscore the need for fresh perspectives on income inequality in economics but also question the ability of democracy to continue providing alternatives for addressing the escalating forms of inequality. Seo and Kang's response to these inquiries diverge from conventional research in several significant ways. Primarily, what sets this research apart from existing studies is its intensified focus on income inequality as a product of the complex interplay between the political and economic domains, rather than a standalone examination of income inequality in isolation. Through a political economy perspective, this book argues that income inequality and income redistribution are shaped by the institutions, policies, and laws generated by the political system, with their formation and nature being determined by the power distribution among socio-political groups. A useful resource not only to researchers who study political phenomena in the field of economics, but also to scholars who study economic phenomena in the field of politics. Furthermore, it will be particularly intriguing for policymakers concerned with issues of inequality and income redistribution"--
Keywords: Income distribution; Democracy -- Economic aspects; BUSINESS & ECONOMICS / Economics / Comparative; BUSINESS & ECONOMICS / Economics / Theory; POLITICAL SCIENCE / Public Policy / Social Policy